Inconsistent Constitutional Court Decisions Resulting in Uncertainty Regarding the Legal Dispute on Regional Head Election Results in Indonesia - Manurung, Saut Parulian (University of Jember, 2019)
In Indonesia, the Constitutional Court is the sole interpreter and guardian of the constitution and the decision made by this Court is expected to meet a sense of justice, utility, and legal certainty. This paper argues that there is a contradiction between two decisions ruled by the Court resulted in inconsistent constitutional interpretations. Such inconsistency can be referred to the decision of the Constitutional Court Number 072-073/PUU-II/2004 declaring the Constitutional Court to have the power to adjudicate disputes over the results of regional head elections, while on the other hand, the decision of the Constitutional Court Number 97/PUU-XI/2013 ruled this institution no longer to adjudicate disputes over the results of regional head elections by revoking Article 236C of the revised Regional Government Act No. 12/2008. In doing so, this paper analyzes the impact of such contradictory decisions on uncertainty in the legal dispute regarding regional head election results. This paper concludes that such inconsistency was caused by the application of two different approaches: the first decision applied judicial activism and the latter considered judicial restraint. Keywords: Constitutional Interpretation, Judicial Restraint, Judicial Activism.